Medusa the mean - Holub, Joan (Holub, Joan. Goddess girls ;, 2012)
"Medusa wants to be more like her two sisters and the other kids at Mount Olympus Academy -- immortal. Is that too much to ask? As one of the few mortals at MOA, it's hard not to get jealous when you're surrounded by beautiful, powerful goddessgirl and godboy classmates. And it isn't easy making friends either, especially when you have snakes for hair and one mean reputation!"--Amazon.